Long-carbon-chain polyamide resin composition as well as preparation method and application thereof
By combining long carbon chain polyamide resin with reinforcement, porcelain formation and ablation filler, the problem of insufficient ablation resistance performance of the battery core material during flame ablation is solved, and high flame retardant, excellent mechanical properties and simplified processing flow are achieved.
Patent Information
- Application Number
- CN202411973910.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
It is difficult for existing battery cell materials to maintain ablation resistance during flame ablation, and there are potential risks such as leakage and flashover, and the processing is complicated and consumes a lot of manpower and material resources.
The long carbon chain polyamide resin composition is used to combine the reinforced filler, porcelain filler and ablation filler to control the content of the resin and filler to form a material with excellent ablation resistance, flame retardant properties and mechanical properties.
It achieves 30 minutes of ablation resistance at high temperature of 800℃, has high flame retardant grade, excellent mechanical properties, avoids leakage and flashover, and simplifies the processing process.
Smart Images

Figure BDA0005220008340000081 
Figure BDA0005220008340000091 
Figure BDA0005220008340000092
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of engineering plastics, and specifically relates to a long carbon chain polyamide resin composition and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid popularization of new energy vehicles, battery thermal runaway fires caused by traffic accidents and bottom collisions have occurred frequently, posing a great threat to the safety of people's lives and property. Therefore, in order to further improve safety performance, new energy vehicles are required to remain powered for a period of time after a fire to facilitate the safe evacuation of personnel. To this end, when a battery cell catches fire, the materials around the battery cell must meet fire resistance requirements to prevent the connection between modules from breaking down after the fire, resulting in leakage and flashover.
[0003] In order to meet the above requirements, mica tape is usually wrapped around the plastic material of the battery cell to provide insulation and ablation resistance. However, this solution is lengthy, complicated to operate, and requires a lot of manpower and material resources. In addition, if the wrapping is not dense in certain locations, there is still a potential risk of leakage and flashover in some locations after ablation.
[0004] Therefore, developing a polyamide material that is resistant to ablation, can be ceramicized during flame ablation, and has good flame retardant and mechanical properties is an urgent problem to be solved in the art. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a long carbon chain polyamide resin composition and a preparation method and application thereof. The long carbon chain polyamide resin composition has good ablation resistance, flame retardancy and mechanical properties and is easy to extrude.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a long carbon chain polyamide resin composition, which comprises, by weight, 35 to 70 parts of a long carbon chain polyamide resin, 4 to 22 parts of a reinforcing filler, 10 to 40 parts of a ceramic filler and 2.5 to 22 parts of an ablative filler; the ceramic filler comprises boron nitride and / or aluminum nitride.
[0008] In the present invention, 35 to 70 parts of the long carbon chain polyamide resin can be, for example, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts or a range between any of the above values, more preferably 45 to 68 parts.
[0009] In the present invention, 4 to 22 parts of reinforcing filler can be, for example, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22 parts or any range between the above values, preferably 5 to 20 parts.
[0010] In the present invention, 10 to 40 parts of the porcelain-forming filler can be, for example, 10 parts, 12 parts, 16 parts, 18 parts, 20 parts, 22 parts, 26 parts, 28 parts, 30 parts, 32 parts, 36 parts, 38 parts, 40 parts or any range between the above values; more preferably 20 to 30 parts.
[0011] In the present invention, 2.5 to 22 parts of ablative filler can be, for example, 2.5, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22 parts or a range between any of the above values, preferably 5 to 20 parts.
[0012] In the present invention, the structure of the ceramic filler is stable and can still maintain good structural stability under ultra-high temperature flame ablation; the ablative filler melts at high temperature, and the ceramic filler in the composite system is bonded and connected into a whole, thereby ensuring the continuity and electrical insulation of the material after high-temperature ablation. The two have a good synergistic effect on improving the flame retardant properties, ablation resistance and porcelain properties of polyamide, and then further compounding the reinforcing filler can improve the ablation resistance of the material, while also ensuring that the material has good mechanical properties.
[0013] Preferably, the long carbon chain polyamide resin comprises semi-aromatic polyamide.
[0014] In the present invention, the long carbon chain polyamide resin includes semi-aromatic polyamide, which can improve the heat resistance and carbonization effect of the material, further improve the ablation resistance, and at the same time is beneficial to improve the strength of the material.
[0015] Preferably, the molecular structure of the long carbon chain polyamide resin comprises a first structural unit and a second structural unit; the first structural unit is a structural unit formed by an aromatic dibasic acid and an aliphatic diamine; the second structural unit is a structural unit formed by an aliphatic diacid having a carbon number ≥ 10 and an aliphatic diamine; the carbon number of the aliphatic diamine in the first structural unit or the second structural unit is ≥ 6.
[0016] In the present invention, the carbon number of the aliphatic diacid is ≥10, for example, it can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 22, 24, 26, 28, 30 or any range between the above values; the carbon number of the aliphatic diamine in the first structural unit or the second structural unit is ≥6, for example, it can be 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 22, 24, 26, 28, 30 or any range between the above values; preferably, the carbon number of the aliphatic dibasic acid is 10-16, and the carbon number of the aliphatic diamine in the first structural unit or the second structural unit is 8-14.
[0017] In the present invention, the aromatic dibasic acid includes at least one of terephthalic acid, isophthalic acid or phthalic acid; the aliphatic diacid having a carbon number ≥ 10 includes at least one of sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid and tetradecanedioic acid.
[0018] In the present invention, the long carbon chain polyamide resin includes a copolymer of terephthalamide and tridecanoyldodecanediamine (PA10T / 1213).
[0019] In the present invention, the mass percentage of the first structural unit in the long carbon chain polyamide resin is 10-60%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or the range between any of the above values, more preferably 20-40%.
[0020] Preferably, the relative viscosity of the long carbon chain polyamide resin is 1.5 to 3.0, for example, it can be 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2, 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, 2.55, 2.6, 2.65, 2.7, 2.75, 2.8, 2.85, 2.9, 3 or the range between any of the above values.
[0021] In the present invention, the relative viscosity is tested in accordance with GB / T 10247-2008.
[0022] In the present invention, the long-chain polyamide resin can be purchased from the market or prepared by conventional methods; illustratively, the preparation method of the long-chain polyamide resin includes: mixing a dibasic acid, a diamine, a monobasic acid (including benzoic acid) and a solvent (including water), reacting for 8 to 16 hours at a temperature of 240 to 290° C. and a pressure of 1 to 5 MPa in the presence of a protective atmosphere to obtain the long-chain polyamide resin; the dibasic acid and the diamine can react directly, or first react to form a salt at 120 to 150° C. for 2 to 5 hours, and then perform a polymerization reaction.
[0023] Preferably, the reinforcing filler includes at least one of glass fiber, carbon fiber, potassium titanate whisker or calcium sulfate whisker.
[0024] Preferably, the ablative filler comprises at least one of zinc borate, boron oxide or glass powder, more preferably glass powder.
[0025] Preferably, the melting temperature of the glass powder is 350-900°C, for example, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 880°C or any range between the above values; preferably 400-700°C.
[0026] In the present invention, the melting temperature of the glass powder can be obtained from the product information provided by the manufacturer, or can be obtained by testing with a differential scanning calorimeter.
[0027] Preferably, the mass ratio of the long carbon chain polyamide resin to the filler is (0.4-2.5):1, wherein the specific value in (0.4-2.5) can be, for example, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5 or a range between any of the above values; more preferably (0.6-1.9):1.
[0028] Preferably, the mass ratio of the reinforcing filler, the porcelain-forming filler and the ablative filler is (0.5-4):(0.5-7):1, wherein the specific value in (0.5-4) can be, for example, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4 or a range between any of the above values; the specific value in (0.5-7) can be, for example, 0.5, 0.6, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7 or a range between any of the above values; more preferably, it is (0.8-1.8):(1.8-5.5):1.
[0029] Preferably, the long carbon chain polyamide resin composition further comprises 0.01 to 30 parts of other additives, by weight, for example, 0.01 parts, 0.05 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 8 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts or a range between any of the above values.
[0030] Preferably, the other auxiliary agents include at least one of an antioxidant, a lubricant or a flame retardant.
[0031] In the present invention, the antioxidant includes but is not limited to at least one of hindered phenol antioxidants, thioester antioxidants, phosphite antioxidants or hindered amine antioxidants; the lubricant includes but is not limited to at least one of magnesium stearate, ethylene bisstearamide or polyethylene wax; the flame retardant includes but is not limited to at least one of melamine derivatives, phosphate flame retardants, ammonium polyphosphate, aluminum hydroxide, magnesium hydroxide, and alkyl hypophosphites.
[0032] In the present invention, the other additives are not limited to the above-mentioned ones, and other types of additives may be added according to actual needs, such as toughening agents, compatibilizers, antistatic agents, carbonizing agents, foaming agents, etc.
[0033] In a second aspect, the present invention provides a method for preparing the long carbon chain polyamide resin composition according to the first aspect, the preparation method comprising the following steps:
[0034] The long carbon chain polyamide resin is mixed with a filler and extruded to obtain the long carbon chain polyamide resin composition.
[0035] Preferably, the mixed material further comprises other auxiliary agents.
[0036] Preferably, the mixing comprises: premixing the long carbon chain polyamide resin, the ablative filler and other optional auxiliary agents, and then adding the reinforcing filler and the ceramic-forming filler for mixing.
[0037] Preferably, the extrusion temperature is 200-280°C.
[0038] In a third aspect, the present invention provides a battery core product, wherein the battery core product comprises the long carbon chain polyamide resin composition described in the first aspect.
[0039] In the present invention, the battery cell product may be, for example, a battery cell busbar plastic shell, which can be used in new energy vehicles.
[0040] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The long-chain polyamide resin composition provided by the present invention is compounded with reinforcing fillers, specific types of porcelain-forming fillers and ablative fillers, and the contents of the long-chain polyamide resin and the fillers are controlled within a specific range, so that the long-chain polyamide resin composition has excellent ablation resistance, can withstand calcination at 800°C for 30 minutes, has a high flame retardant grade, and has good mechanical properties. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0044] In the present invention, the materials used in the examples and comparative examples are all commercially available or prepared by conventional methods. Unless otherwise specified, the materials used in the present invention are as follows:
[0045] Long carbon chain polyamide resin (PA)
[0046] PA-1: a copolymer of 10T (10T) and 1213 (10T-10T) tridecanoyl dodecane diamine (1213), PA10T / 1213; wherein the mass percentage of the 10T structural unit is 30%, and the preparation method is as follows.
[0047] (1) reacting dodecanediamine and tridecanediacid at 130° C. for 3 h to obtain amide salt A; wherein the molar ratio of dodecanediamine to tridecanediacid is 1:1;
[0048] (2) reacting terephthalic acid and decanediamine at 140° C. for 5 hours to obtain amide salt B; wherein the molar ratio of terephthalic acid to decanediamine is 1:1;
[0049] (3) Amide salt A and amide salt B (the mass ratio of amide salt A to amide salt B is 7:3) are mixed with benzoic acid and water, and added into a reactor with a nitrogen atmosphere and a pressure of 2.5 MPa, and reacted at 260° C. for 12 hours to obtain the PA10T / 1213; the molar content of the benzoic acid is 1.5 mol% of the total molar amount of amide salt A and amide salt B, and the mass of the water is 20 wt% of the total mass of the raw materials (the raw materials refer to the components used including water).
[0050] Among them, the mass content of 10T structural units in polyamide resin can be tested by nuclear magnetic resonance hydrogen spectrometer and calculated by the integral area ratio of characteristic peaks.
[0051] PA-2: The only difference between it and PA-1 is that the mass percentage of 10T structural unit is 15%, and the mass ratio of amide salt A to amide salt B in the preparation method is 8.5:1.5.
[0052] PA-3: The only difference between it and PA-1 is that the mass percentage of 10T structural unit is 55%, and the mass ratio of amide salt A to amide salt B in the preparation method is 4.5:5.5.
[0053] PA-4: The only difference between PA-4 and PA-1 is that terephthalic acid is replaced by an equal molar amount of sebacic acid.
[0054] Reinforcement filler
[0055] Fiberglass: Jushi E7CS10-03-568H.
[0056] Carbon fiber: Osaka Gas Chemical S-232.
[0057] Potassium titanate whiskers: Otsuka Chemical TISMO D102.
[0058] Porcelain Filling
[0059] Boron nitride: PT110 from Shanghai Jichuan Trading Co., Ltd.
[0060] Aluminum nitride: Japan Toyo Aluminum TFZ-S05P.
[0061] Mica: Huajing Mica C-50.
[0062] Wollastonite: Jiangxi Guangyuan GY-2000.
[0063] Ablative filler
[0064] Glass powder 1: melting temperature is 450℃, Chuanguo powder BL-45.
[0065] Glass powder 2: melting temperature is 600℃, Chuanguo powder BL-60.
[0066] Glass powder 3: The melting temperature is 850°C and it was purchased from Chuanguo Powder BL-85.
[0067] Glass powder 4: melting temperature is 380°C, purchased from Chuanguo Powder BL-38.
[0068] Zinc borate: Henan Dingxiang Chemical ZB-2335.
[0069] Other additives: antioxidant tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, lubricant ethylene bisstearamide.
[0070] Flame retardant: a mixture of diethyl aluminum hypophosphite (Clariant flame retardant Exolit OP 1230) and melamine cyanurate (Hongtaiji) in a mass ratio of 1:1.
[0071] Foaming agent: potassium carbonate, Henan Bafos, particle size is 200 mesh.
[0072] Carbon former: triazine carbon former, Yinyuan New Materials FR-CFA.
[0073] Examples 1 to 16, Comparative Examples 1 to 2
[0074] Examples 1 to 16 and Comparative Examples 1 to 2 respectively provide a polyamide resin composition, and the compositions of the polyamide resin composition are shown in Tables 1 to 4 in parts by weight; wherein, “ / ” indicates that the component is not included in the formula.
[0075] In the present invention, unless otherwise specified, the preparation method of the polyamide resin composition comprises: premixing a polyamide resin, an ablative filler and optional other additives, and adding them from the main feeding port of a twin-screw extruder; adding a porcelain-forming filler from the first side feeding port of the twin-screw extruder, adding a reinforcing filler from the second side feeding port of the twin-screw extruder, melt blending, extruding and granulating to obtain the long polyamide resin composition; wherein the temperature settings of different intervals of the twin-screw extruder are 230°C, 240°C, 240°C, 250°C, 250°C, 240°C, 240°C, 240°C, 260°C, and 270°C, respectively.
[0076] Table 1
[0077]
[0078]
[0079] Table 2
[0080]
[0081] Table 3
[0082]
[0083]
[0084] Table 4
[0085]
[0086] Performance Testing
[0087] (1) Flame retardant properties: The polyamide resin compositions provided in Examples 1 to 16 and Comparative Examples 1 to 2 were molded into strips with a specification of 125×13×0.8 mm at an injection molding temperature of 265° C. The vertical burning properties of the strips were tested according to UL94 standard, and the flame retardant levels were recorded.
[0088] (2) Ablation resistance: The polyamide resin compositions provided in Examples 1 to 16 and Comparative Examples 1 to 2 were molded into strips of 100×100×1 mm at an injection molding temperature of 265° C. The strips were placed in a muffle furnace and calcined for 30 min at 800° C. The strips were then observed for burn-through, cracking, and the like. Among them, if the strips had no burn-through or cracking, it was recorded as 1; if the strips had cracking or burn-through, it was recorded as 2; if the strips had burn-through and cracking, it was recorded as 3.
[0089] (3) Mechanical properties: The polyamide resin compositions provided in Examples 1 to 16 and Comparative Examples 1 to 2 were molded into dumbbell-shaped strips with a thickness of 4 mm at an injection molding temperature of 265° C. The tensile strength and elongation at break of the strips were tested according to ISO527--2-2012 standard, and the tensile rate was 5 mm / min.
[0090] The specific test results are shown in Table 5.
[0091] Table 5
[0092]
[0093] As can be seen from Table 5, the long-chain polyamide resin composition provided by the present invention is compounded with reinforcing fillers, specific types of ceramic fillers and ablative fillers, and the contents of the long-chain polyamide resin and the filler are controlled within a specific range, so that the long-chain polyamide resin composition has excellent ablation resistance, high flame retardancy and good mechanical properties.
[0094] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A long carbon chain polyamide resin composition, characterized in that In parts by weight, the long carbon chain polyamide resin composition comprises 35 to 70 parts of long carbon chain polyamide resin, 4 to 22 parts of reinforcing filler, 10 to 40 parts of porcelain-forming filler and 2.5 to 22 parts of ablative filler; The ceramic-forming filler comprises boron nitride and / or aluminum nitride.
2. The long carbon chain polyamide resin composition according to claim 1, characterized in that: The polyamide resin includes semi-aromatic polyamide; Preferably, the molecular structure of the long carbon chain polyamide resin comprises a first structural unit and a second structural unit; the first structural unit is a structural unit formed by an aromatic dibasic acid and an aliphatic diamine; the second structural unit is a structural unit formed by an aliphatic diacid having a carbon number ≥ 10 and an aliphatic diamine; the carbon number of the aliphatic diamine in the first structural unit or the second structural unit is ≥ 6; Preferably, the carbon number of the aliphatic dibasic acid is 10-16, and the carbon number of the aliphatic diamine in the first structural unit or the second structural unit is 8-14.
3. The polyamide resin composition according to claim 2, characterized in that The mass percentage of the first structural unit in the long carbon chain polyamide resin is 10 to 60%, more preferably 20 to 40%.
4. The long carbon chain polyamide resin composition according to any one of claims 1 to 3, characterized in that: The reinforcing filler includes at least one of glass fiber, carbon fiber, potassium titanate whisker or calcium sulfate whisker.
5. The long carbon chain polyamide resin composition according to any one of claims 1 to 4, characterized in that: The ablative filler comprises at least one of zinc borate, boron oxide or glass powder, preferably glass powder; Preferably, the melting temperature of the glass powder is 350-900°C, more preferably 400-700°C.
6. The long carbon chain polyamide resin composition according to any one of claims 1 to 5, characterized in that: The mass ratio of the long carbon chain polyamide resin to the filler is (0.4-2.5):1, and more preferably (0.6-1.9):
1.
7. The long carbon chain polyamide resin composition according to any one of claims 1 to 6, characterized in that: The long carbon chain polyamide resin composition further comprises 0.01 to 30 parts by weight of other additives; Preferably, the other auxiliary agents include at least one of an antioxidant, a lubricant or a flame retardant.
8. A method for preparing the long carbon chain polyamide resin composition according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The long carbon chain polyamide resin is mixed with a filler and extruded to obtain the long carbon chain polyamide resin composition.
9. The preparation method according to claim 8, characterized in that: The mixed material also includes other additives; Preferably, the mixing comprises: premixing the long carbon chain polyamide resin and the ablative filler and optionally other auxiliary agents, and then adding the reinforcing filler and the porcelain-forming filler for mixing; Preferably, the extrusion temperature is 200-280°C.
10. A battery cell product, characterized in that: The battery core product comprises the long carbon chain polyamide resin composition according to any one of claims 1 to 7.
Citation Information
Patent Citations
Polyamide resin composition with improved properties
KR1020000072455A
Cited By
Flame-retardant reinforced bio-based nylon composite material with high CTI (comparative tracking index) value and preparation method thereof
CN121006065A
ABS composite material as well as preparation method and application thereof
CN121628280A